Supporting Business Opportunities for Rural Women in East and Southern Africa: A case study of Uganda - Kavuma, Susan Namirembe; Muhanguzi, Florence Kyoheirwe; Bogere, George; Cunningham, Kiran (ACODE Policy Research Series, 2018)
This study examines the characteristics of rural women doing business in Uganda. It analyses the nature of business operations and structural barriers women face thus hindering them from seizing economic opportunities. It is part of a collaborative research project on ”Supporting Opportunities for Rural Women in Business in East and Southern Africa” implemented in three countries: Zimbabwe, Kenya and Uganda. The baseline study informs the design of the proposed intervention to support rural women in business. It also establishes the key parameters to be measured during the endline survey. Three research institutions were contracted to implement this project: the Institute of Environmental Studies (IES) in Zimbabwe, the Collaborative Centre for Gender and Development (CCGD) in Kenya, and Advocates Coalition for Development and Environment (ACODE) in Uganda. The overall aim of this research is to support the economic empowerment of rural women in value addition businesses in the three countries. This will be achieved through identification and promotion of viable business enterprises that lead to the creation of decent and sustainable jobs. In this research, we conceptualise women empowerment in two major dimensions: economic advancement, and power and agency. Expounded by Golla et al. (2011), women’s economic empowerment is defined as the ability of women to succeed and advance economically and possess the power to make and act on economic decisions. For economic empowerment, women must have access to productive resources such as human capital (education, skills and training), financial capital (loans, savings), physical capital (land, machinery), and social capital (networks and mentors). Women must also have the power and agency necessary to make and act on decisions regarding the distribution and control of resources and proceeds from business ventures. This conceptual framework is the basis of our theory of change and the proposed intervention to empower women in the study sites. The intervention is designed to empower women through a combination of mentorship and peer to peer learning to improve their basic business skills and their capacity for product development, both of which were identified as areas of need by women who participated in the baseline study. Through this intervention, women will have greater ability to access productive resources and improve their capacity for agency and wellbeing.